Management of Hutumuri Village Infographics by Using Statistical Data - Latupeirissa, Sanlly Joanne; Salhuteru, Rosalina; J. Wattimanela, Henry; Lembang, Ferry Kondo; J. Djami, Ronald; Y. Matdoan, Muhammad; S Laamena, Novita; Yudistira, Yudistira (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
The problem of Hutumuri village officials is that they are limited in presenting data visually so that the available data is difficult to understand by the community. Therefore, the team decided to provide training to Hutumuri village officials in managing and utilizing population statistics data to create effective and attractive infographics. Village officials were trained to understand the basics of statistics, how to interpret data, and techniques for creating infographics using MS Excel. The training also covered data visualization concepts, such as the selection of colors, typography, and icons to make infographics attractive. Infographics are used to publish population statistics in Hutumuri Village, and village officials can easily present data in visual form at meetings or community gatherings. By this community service activity, village officials better understand the concept of population statistics data, can calculate and present population statistics in Hutumuri Village.